Mechanical properties experiment of load capacity on a mechanical yielding steel prop (MYSP) and its application in roadway support - Chen, Yanlong; Hai, Pu; Peng, Wu; Wu, Haoshuai; Yu, Wu; Yang, Hao; Goh, Thian Lai; Azrin Azmi; Abdurrahman, Muslim (Penerbit Universiti Kebangsaan Malaysia, 2020)
As the coal mining depth increases year by year, the deformation and failure of deep roadway become more serious. Therefore, new support equipment with high supporting force and yieldable character is quite necessary for mining safety. In this research, a new mechanical yielding steel prop (MYSP) with high stable load capacity was introduced, which features sustaining large deformation in the field. The test shows that the load capacity provided by doublelayer steel balls is greater than that of single-layer steel balls, and that provided by high-hardness steel balls is higher than that of low-hardness steel balls. When double-layer high-hardness steel balls are adopted, the load capacity firstly increases and then remains stable with the increase of displacement, while it firstly increases and then decreases and finally remains stable with the increase of displacement when double-layer low-hardness steel balls are adopted. The load capacity decreases with the increase of inclined angle of the outer tube, but the influence of the inclined angle of the outer tube on load capacity provided by high-hardness steel balls is small. The load capacity increases gradually with the yielding strength of the prop. Therefore, the MYSP with different load capacities can be designed by changing the yielding strength of the outer tube and inner tube. The field application shows that the MYSP has good characteristics of yielding and high constant resistance. It is very effective for controlling the deformation of surrounding rock mass using the MYSP for roadway pre-support, which also reduces the supporting cost significantly.